2010
DOI: 10.1093/jac/dkq068
|View full text |Cite
|
Sign up to set email alerts
|

Intrafamilial transmission of extended-spectrum- -lactamase-producing Escherichia coli and Salmonella enterica Babelsberg among the families of internationally adopted children

Abstract: International travellers, transfer of patients and now adoption may contribute to the global emergence of MDR bacteria. Thus, in addition to the usual screening of adopted children for infectious diseases, additional screening for MDR bacteria should be recommended, at least for children coming from countries with a high prevalence of MDR bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 31 publications
3
40
2
Order By: Relevance
“…This contrasts with the mean carriage duration of 6.6 months in patients who were colonized during hospitalization (94). However, carriage can be far more prolonged in travelers with diarrhea or exposed to antibiotics while abroad (93,95) and in native African children arriving in Europe after adoption (96).…”
Section: Travelersmentioning
confidence: 87%
See 1 more Smart Citation
“…This contrasts with the mean carriage duration of 6.6 months in patients who were colonized during hospitalization (94). However, carriage can be far more prolonged in travelers with diarrhea or exposed to antibiotics while abroad (93,95) and in native African children arriving in Europe after adoption (96).…”
Section: Travelersmentioning
confidence: 87%
“…In China, the carriage rates were higher in families with at least one individual with a history of out-of-town residence and were inversely correlated with living space (98). Finally, transmission of ESBL-E within the family does not seem to be limited to E. coli but may also occur for other enterobacteria, such as Salmonella (96).…”
Section: Dissemination Routes Strain Diversity and Transmissionmentioning
confidence: 94%
“…Our data are in agreement with previous studies, which found a prevalence of multidrug-resistant bacteria in adults from developing countries. 7,8,25 The hypotheses for this prevalence are frequent self-medication with poor quality drugs that are given without control by the health authorities and inadequate drug dosage or treatment duration.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][78][79][80][81][82][83][84][85][86][87][88][89][90] Most studies were conducted in the acute-care setting [21][22][23][79][80][81]83,85,87,[89][90][91] and identified a population of patients infected and/or colonized with MDR-E, either ESBL-E or CRE, or MDR-Enterobacteriaceae defined by resistance to multiple classes of drugs. Patients were assessed for persistence of colonization at study-specific intervals and variable durations of follow-up.…”
Section: Duration Of Colonizationmentioning
confidence: 99%